Dimethyl Fumarate Combined With Vemurafenib Enhances Anti-Melanoma Efficacy via Inhibiting the Hippo/YAP, NRF2-ARE, and AKT/mTOR/ERK Pathways in A375 Melanoma Cells - Li, Hongxia; Wang, Yaping; Su, Rina; Jia, Yuchen; Lai, Xiong; Su, Huimin; Fan, Yaochun; Wang, Yuewu; Xing, Wanjin; Qin, Jianzhong (Frontiers in Oncology, 2022)
Melanoma is a deadly form of skin cancer with high rates of resistance to traditional chemotherapy and radiotherapy. BRAF inhibitors (BRAFi) can achieve initial efficacy when used to treat melanoma patients, but drug resistance and relapse are common, emphasizing the need for new therapeutic strategies. Herein, we reported that combination of dimethyl fumarate (DMF) and vemurafenib (Vem) inhibited melanoma cell proliferation more significantly and induced more cell death than single agent did both in vitro and in vivo. DMF/Vem treatment induced cell death through inhibiting the expression and transcriptional activity of NRF2 thereby resulting in more reactive oxygen species (ROS) and via inhibiting the expression of YAP, a key downstream effector of Hippo pathway. DMF/Vem treatment also reduced phosphorylation of AKT, 4EBP1, P70S6K and ERK in AKT/mTOR/ERK signaling pathways. RNA-seq analysis revealed that DMF/Vem treatment specifically suppressed 4561 genes which belong to dozens of cell signaling pathways. These results indicated that DMF/Vem treatment manifested an enhanced antitumor efficacy through inhibiting multiple cell signaling pathways, and thus would be a novel promising therapeutic approach targeted for melanoma.